Jupiter [compact disc] : the planet, satellites, and magnetosphere - Bagenal, Fran, 1954-; Dowling, Timothy E. (Timothy Edward), 1962-; McKinnon, William B. (Cambridge, UK : Cambridge University Press, 2004)
26